2023
DOI: 10.1177/20406223221143239
|View full text |Cite
|
Sign up to set email alerts
|

How do phytocannabinoids affect cardiovascular health? An update on the most common cardiovascular diseases

Abstract: Cardiovascular disease (CVD) causes millions of deaths worldwide each year. Despite the great progress in therapies available for patients with CVD, some limitations, including drug complications, still exist. Hence, the endocannabinoid system (ECS) was proposed as a new avenue for CVDs treatment. The ECS components are widely distributed through the body, including the heart and blood vessels, thus the action of its endogenous and exogenous ligands, in particular, phytocannabinoids play a key role in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…Preclinical studies in rats have reported a reduced heart rate in response to CBN; however, this effect has not been found in humans ( 62 , 63 ). The potential cardioprotective effects of CBNs could be related to agonistic interactions with CB2_Rs, TRPV1, and TRPV2 ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in rats have reported a reduced heart rate in response to CBN; however, this effect has not been found in humans ( 62 , 63 ). The potential cardioprotective effects of CBNs could be related to agonistic interactions with CB2_Rs, TRPV1, and TRPV2 ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Table [8] revealed that there were no significant correlations in the cannabis user group at admission and after treatment between creatinine and CWAS, tetrahydrocannabinol level, age, and duration of cannabis intake.…”
Section: Plos Onementioning
confidence: 91%
“…Exposure to Cannabis raises the heart rate and blood pressure and can sometimes cause orthostatic hypotension. Cannabis users have reported severe cardiac problems, including acute coronary syndromes and strokes [8].…”
Section: Introductionmentioning
confidence: 99%